The functional state of patients with fractures of the shin bones treated with help of the Matsukidis-Shevtsov device - Schurov, Vladymyr; Matsukatov, Fedor (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2013)
The examination involved 223 patients with closed fractures of the shin bones during treatment with help of the Matsukidis-Shevtsov device, which provided less micromobility on bone fragment junctions in conditions of axial loading on the extremity versus bone fixing with help of the Ilizarov device (130 cases). In patients over 40, who suffered from comminuted fractures, during the first month after the injury a higher blood velocity increment in their regeneration region was revealed in cases of oxygen pressure decrease below 5.32 MPa. The restoration of the contractile properties of muscles, functional loading on the extremity and psychoemotional state of the patient occurred most actively during the first 2 years after the end of treatment.